Examining the Relationship Between Digital Transformation and Work Quality: Substitution Potential and Work Exposure in Gender-Specific Occupations - Katharina Dengler; Anita Tisch (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Computers can substitute for many tasks currently performed by humans and are likely to change occupations in the near future. However, it is not likely that entire occupations will disappear. In this context, little attention has been paid to possible impacts of digital transformation on aspects of work quality. It would be desirable for changes to ease occupations with high work exposure. In this article, we assume that digital technologies may replace physically demanding jobs mainly performed by men, but not psychosocially demanding jobs mainly performed by women. Thus, the question arises whether social inequality between men and women may increase in the course of digital transformation. Using large-scale administrative and survey data from Germany, we analyse the relationship between digital transformation and work exposure for male- and female-dominated occupations. We measure the degree of digital transformation by occupation-specific substitution potential, that is the extent to which occupational tasks can be replaced by computers or computer-controlled machines. The results imply that digital technologies could relieve men of physically demanding jobs. However, we cannot find any evidence that digital technologies have already caused employment to decline in occupations with physical work exposure.
Keywords: 300; Technological change; Automation; Work load; Gendered occupations; Germany; Technologischer Wandel; Automatisierung; Arbeitsexposition; Geschlechtsspezifische Berufe; Deutschland